Optimalisasi Kesejahteraan Psikologis Relawan Bencana Melalui Pelatihan Mindfulness - Ahmad, Masnaeni; Hardiyati Hardiyati; Ali Salaka, Syafruddin (Pusat Riset dan Inovasi Nasional, 2023)
Due to their dual roles as disaster survivors and disaster volunteers who aid communities devastated by disasters, disaster volunteers are susceptible to experiencing a decline in the quality of their psychological well-being. The ultimate objective of mindfulness is to make it easier to stay engaged in the present without overestimating it. This program intends to provide mindfulness training in an effort to improve the volunteers' psychological well-being throughout disasters. Focused Group Discussions, education, and training are all used as community empowerment techniques in this work. The 20 BPBD disaster volunteers from the West Sulawesi Province are the target. Activities to enhance the psychological well-being of disaster volunteers can increase knowledge by 53% while also improving the psychological well-being of volunteers by giving education and mindfulness training. For both disaster volunteers and society, mindfulness training could be an important supplement to the disaster training curriculum.